Protein-Protein Interactions in Candida albicans - Schoeters, Floris; Van Dijck, Patrick (Frontiers in Microbiology, 2019)
Despite being one of the most important human fungal pathogens, Candida albicans has not been studied extensively at the level of protein-protein interactions and data on PPIs are not readably available in online databases. In January 2018, the database called “Biological General Repository for Interaction Datasets (BioGRID)” that contains the most PPIs for C. albicans only contained 188 (physical, direct) protein-protein interactions (PPIs) (release 3.4.156) while several more PPIs detected in C. albicans can be found in the literature. Other databases such as The String database, The Molecular INTeraction Database (MINT), and The DIP database contain even les interactions or do not even include C. albicans as a searchable term. Because of the aberrant codon usage of C. albicans, CUG is translated in serine rather than leucine, it is less optimal to use the yeast two-hybrid system in Saccharomyces cerevisiae to study C. albicans PPIs. However studying PPIs is crucial to know more about the function of proteins, biological processes and pathways. PPIs can also be potential drug targets. To aid in creating PPI networks and updating the BioGRID we performed an exhaustive literature search in order to expand the list of known PPIs in C. albicans substantially.